Epigallocatechin Gallate Attenuates Proliferation and Oxidative Stress in Human Vascular Smooth Muscle Cells Induced by Interleukin-1<svg xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg" style="vertical-align:-4.445701pt" id="M1" height="17.2385pt" version="1.1" viewBox="-0.0657574 -12.7928 10.9916 17.2385" width="10.9916pt"><g transform="matrix(.018,0,0,-0.018,0,0)"><path id="g5-224" d="M584 573C584 646 528 703 441 703C387 703 327 679 274 632C202 568 166 493 132 302L57 -122C43 -201 35 -214 21 -227L25 -246C54 -244 122 -236 156 -203C168 -191 175 -162 195 -40L261 369C291 556 318 652 391 652C431 652 465 620 465 543C465 497 449 456 408 422C395 411 364 405 340 403L309 336C386 319 447 279 447 188C447 105 419 50 329 50C290 50 253 63 226 77L216 55C218 23 252 -16 286 -16C324 -16 369 3 419 31C488 69 575 149 575 238C575 325 516 369 437 400C516 443 584 486 584 573Z"/></g> via Heme Oxygenase-1 - Liu, Po-Len; Liu, Jung-Tung; Kuo, Hsuan-Fu; Chong, Inn-Wen; Hsieh, Chong-Chao (Mediators of Inflammation, 2014)
Proliferation of vascular smooth muscle cells (VSMCs) triggered by inflammatory stimuli and oxidative stress contributes importantly to atherogenesis. The association of green tea consumption with cardiovascular protection has been well documented in epidemiological observations, however, the underlying mechanisms remain unclear. This study aimed to elucidate the effects of the most active green tea catechin derivative, (−)-epigallocatechin-3-gallate (EGCG), in human aortic smooth muscle cells (HASMCs), focusing particularly on the role of a potent anti-inflammatory and antioxidative enzyme heme oxygenase-1 (HO-1). We found that pretreatment of EGCG dose- and time-dependently induced HO-1 protein levels in HASMCs. EGCG inhibited interleukin- (IL-)1β-induced HASMC proliferation and oxidative stress in a dose-dependent manner. The HO-1 inducer CoPPIX decreased IL-1β-induced cell proliferation, whereas the HO-1 enzyme inhibitor ZnPPIX significantly reversed EGCG-caused growth inhibition in IL-1β-treated HASMCs. At the molecular level, EGCG treatment significantly activated nuclear factor erythroid-2-related factor (Nrf2) transcription activities. These results suggest that EGCG might serve as a complementary and alternative medicine in the treatment of these pathologies by inducing HO-1 expression and subsequently decreasing VSMC proliferation.